An ELISA Assay for Quantifying Monomeric C-Reactive Protein in Plasma - Zhang, Lin; Li, Hai-Yun; Li, Wei; Shen, Zhi-Yuan; Wang, Yin-Di; Ji, Shang-Rong; Wu, Yi (Frontiers in Immunology, 2018)
Native C-reactive protein (nCRP) is a non-specific marker of inflammation being claimed as a bystander in several chronic disorders. Accumulating evidence indicates that nCRP dissociates to and acts primarily as the monomeric conformation (mCRP) at inflammatory loci. This suggests that mCRP may be a superior disease marker with improved specificity and clear causality to the underlying pathogenesis. However, the lack of a feasible assay to quantify mCRP in clinical samples precludes the assessment of that suggestion. Here we report the development of a sandwich ELISA assay for quantification of plasma mCRP using commercially available reagents. Our assay is reproducible and highly conformation-specific showing a reliable detection limit of 1 ng/mL. We further show that mCRP appears to be a better marker than nCRP in several skin-related autoimmune disorders. This assay thus provides a useful tool to examine the clinical significance and utility of mCRP.